Budgetary participation’s antecedent of information asymmetry and its outcomes - Ngo, Quang-Huy (Penerbit Universiti Kebangsaan Malaysia, 2019)
The purpose of this study is to investigate the antecedents and outcomes of budgetary participation. More specifically, I propose that a lack of information fosters budgetary participation. A high degree of participation allows the managers to have a favourable attitude toward budget attained and in turn, this leads to a low degree of budgetary creation slack. The questionnaire data obtained from 115 Vietnamese managers was used to test the proposed model. The results suggest that highly asymmetric information demands high participative budgeting. When participating more in the budgeting process, the managers’ attitude toward the budget attained was favourable, and in turn, this leads to the decrease of budgetary slack creation. These findings contribute to the budgeting literature in a threefold manner. First, this study supports the argument that the demand for participation is high when there is highly asymmetric information. Second, the results suggest that the managers’ attitude toward the budget attained mediates the relationship between budgetary participation and the managers’ creation of budgetary slack. Third, by using the theory of planned behaviour, this study has explained how and why a favourable attitude toward the budget attained leads to the low creation of budgetary slack.